Bendamustine plus rituximab versus fludarabine plus rituximab for patients with relapsed indolent and mantle-cell lymphomas: a multicentre, randomised, open-label, non-inferiority phase 3 trial. Issue 1 (January 2016) - Rummel, Mathias; Kaiser, Ulrich; Balser, Christina; Stauch, Martina; Brugger, Wolfram; Welslau, Manfred; Niederle, Norbert; Losem, Christoph; Boeck, Hans-Peter; Weidmann, Eckhart; von Gruenhagen, Ulrich; Mueller, Lothar; et al.
Summary: Background: Fludarabine-based chemoimmunotherapy with rituximab is frequently used in patients with indolent and mantle-cell lymphomas who relapse after alkylating chemotherapy. We aimed to compare the efficacy and safety of rituximab with bendamustine or fludarabine in patients with relapsed, indolent, non-Hodgkin lymphoma and mantle-cell lymphoma. Methods: For this randomised, non-inferiority, open-label, phase 3 trial, we recruited patients from 55 centres in Germany, who were subsequently randomised centrally according to prespecified randomisation lists with permuted blocks of randomly variable block size to rituximab (375 mg/m 2, day 1) plus either bendamustine (90 mg/m 2, days 1 and 2) or fludarabine (25 mg/m 2, days 1–3) every 28 days for a maximum of six 28-day cycles. Patients were aged 18 years or older with a WHO performance status of 0–2 and had relapsed or refractory indolent or mantle-cell lymphoma; patients refractory to regimens that included rituximab, bendamustine, or purine analogue drugs were excluded. Patients were stratified by histological subtypes of lymphoma and by their latest previous therapies. Treatment allocation was not masked. The primary endpoint was progression-free survival and the final analysis was completed per protocol. Non-inferiority of bendamustine plus rituximab versus fludarabine plus rituximab was defined as a difference of less than 15% in 1-year progression-free survival. The protocol was amended in July, 2006, after approval of rituximab maintenance (375 mg/m 2 every 3 months for up to 2 years), which was then given to patients achieving a response to either trial treatment. This study is registered with ClinicalTrials.gov, number NCT01456351 (closed to enrolment, follow-up is ongoing). Findings: Between Oct 8, 2003, and Aug 5, 2010, we randomly assigned 230 patients to treatment groups (116 bendamustine plus rituximab, 114 fludarabine plus rituximab). 11 patients were excluded for protocol violations and were not followed up further (two in the bendamustine plus rituximab group and nine in the fludarabine plus rituximab group). Thus, 219 patients were included in the per-protocol analysis (114 bendamustine plus rituximab, 105 fludarabine plus rituximab). 1-year progression-free survival with bendamustine plus rituximab was 0·76 (95% CI 0·68–0·84) and 0·48 (0·39–0·58) with fludarabine plus rituximab (non-inferiority p<0·0001). At a median follow-up of 96 months (IQR 73·2–112·9), median progression-free survival with bendamustine plus rituximab was 34·2 months (95% CI 23·5–52·7) and 11·7 months (8·0–16·1) with fludarabine plus rituximab (hazard ratio [HR] 0·54 [95% CI 0·38–0·72], log-rank test p<0·0001). Safety outcomes were similar in both groups, with 46 serious adverse events recorded (23 in the bendamustine plus rituximab group and 23 in the fludarabine plus rituximab group), most commonly myelosuppression and infections. Interpretation: In combination with rituximab, bendamustine was more effective than fludarabine, suggesting that bendamustine plus rituximab may be the preferred treatment option for patients with relapsed indolent and mantle-cell lymphomas. Funding: Roche Pharma AG, Ribosepharm GmbH, Mundipharma GmbH, Studiengruppe indolente Lymphome (StiL).